Contextual Study: Improving Student Learning Outcomes to Comprehend Educational Successes and Strategies - Makhijani, Simran Roopam; Dugaje, Manohar D (Pascasarjana Universitas Negeri Makassar, 2024)
This study examines the many challenges students face in Nashik district schools in Maharashtra, India and it emphasizes quality education process to shape individual trajectories and contribute to national progress. The paper carefully examines financial constraints, behavioral issues, digital distractions, mental health issues, and emotional challenges that affect students' academic journeys. Critical analysis is also done in considering the origins of these challenges, including the British colonial era and the post-independence education system. This historical contextualization shows that historical and systemic factors have woven modern educational challenges. The study explores Nashik district's education, highlighting socioeconomic, gender, and geographical disparities and these disparities perpetuate cycles of inequity and hinder educational potential. The paper goes beyond problem identification as it promotes systemic changes and comprehensive solutions. These solutions include policy reforms, infrastructure improvements, teacher capacity-building, and community collaboration. This multi-faceted approach aims to address these issues at their core, creating a paradigm shift that could change Nashik district students' educational trajectory. Moreover, the research paper advocates for an inclusive, empowering, and challenging educational environment that empower students from all backgrounds. This paper envisions a brighter future for Nashik district, where each student's educational journey is marked by resilience, growth, and a transformative impact on personal lives and society. The paper's rigorous exploration, contextualization, and advocacy aim to spark a substantive dialogue that resonates deeply in Nashik's educational ecosystem.